Impact of Medical Qigong on quality of life, fatigue, mood and inflammation in cancer patients: A randomized controlled trial - Oh, B.; Butow, P.; Mullan, Barbara; Clarke, S.; Beale, P.; Pavlakis, N.; Kothe, E.; Lam, L.; Rosenthal, D. (Oxford University Press, 2010)
Background: Substantial numbers of cancer patients use complementary medicine therapies, even without a supportive evidence base. This study aimed to evaluate in a randomized controlled trial, the use of Medical Qigong (MQ) compared with usual care to improve the quality of life (QOL) of cancer patients. Patients and methods: One hundred and sixty-two patients with a range of cancers were recruited. QOL and fatigue were measured by Functional Assessment of Cancer Therapy—General and Functional Assessment of Cancer Therapy—Fatigue, respectively, and mood status by Profile of Mood State. The inflammatory marker serum C-reactive protein (CRP) was monitored serially. Results: Regression analysis indicated that the MQ group significantly improved overall QOL (t144 = 25.761, P < 0.001), fatigue (t153 = 25.621, P < 0.001), mood disturbance (t122 =2.346, P = 0.021) and inflammation (CRP) (t99 = 2.042, P < 0.044) compared with usual care after controlling for baseline variables. Conclusions: This study indicates that MQ can improve cancer patients’ overall QOL and mood status and reduce specific side-effects of treatment. It may also produce physical benefits in the long term through reduced inflammation.